Sample cells for probing solid/liquid interfaces with broadband sum-frequency-generation spectroscopy - Verreault, Dominique; Kurz, Volker L.; Howell, Caitlin; Kölsch, Patrick (Review of scientific instruments, 2010)
Two sample cells designed specifically for sum-frequency-generation (SFG) measurements at the solid/liquid interface were developed: one thin-layer analysis cell allowing measurement of films on reflective metallic surfaces through a micrometer layer of solution and one spectroelectrochemical cell allowing investigation of processes at the indium tin oxide/solution interface. Both sample cells are described in detail and data illustrating the capabilities of each are shown. To further improve measurements at solid/liquid interfaces, the broadband SFG system was modified to include a reference beam which can be measured simultaneously with the sample signal, permitting background correction of SFG spectra in real time. Sensitivity tests of this system yielded a signal-to-noise ratio of 100 at a surface coverage of 0.2 molecules/nm2. Details on data analysis routines, pulse shaping methods of the visible beam, as well as the design of a purging chamber and sample stage setup are presented. These descriptions will be useful to those planning to set up a SFG spectrometer or seeking to optimize their own SFG systems for measurements of solid/liquid interfaces.